Prescribing Pattern in Outpatient Departments of Two Tertiary Care Teaching Hospitals in Dhaka (Journal of Enam Medical College, 2015)
Background: Medically inappropriate, ineffective and economically inefficient use of drugs is very common in our country. About 40% or more drugs expenditure may be wasted through irrational prescribing and dispensing. The need for promoting rational use of drugs is not only because of economic considerations; also it is an essential element for achieving quality of the health and medical care for patients and the community. For this purpose a cross sectional study was carried out among the individuals attending the outpatient departments (OPD) of Medicine, Surgery, Gynecology & Obstetrics, Pediatrics, Orthopedics, Dermatology & Venereology, Ophthalmology and Otolaryngology of two tertiary care teaching hospitals of Dhaka, Bangladesh.Objective: To observe the prescribing pattern in outpatient departments of two tertiary care teaching hospitals (Dhaka) by using World Health Organization (WHO) core prescribing indicators.Materials and Methods: Six hundred prescriptions of patients attending the OPD of Medicine, Surgery, Gynecology & Obstetrics, Pediatrics, Orthopedics, Dermatology & Venereology, Ophthalmology and Otolaryngology of Enam Medical College Hospital (private hospital) and Sir Salimullah Medical College Hospital (public hospital) were collected randomly on working days from April to September 2014. Then the prescriptions were analyzed by following the Prescribing indicators form as recommended by the International Organization of Rational Use of Drugs (INRUD)/WHO.Results: Average number of drugs per prescription was significantly high (3.07 in public hospital and 3.00 in private hospital). Generic prescribing was significantly lower in private hospital (4.00%) than that in public hospital (21.00%). Antibiotic prescription was higher in private hospital (42.35%). Injection prescribed in public hospital was 5.74% whereas 5.66% in private hospital. Drugs prescribed from Essential Drug List of Bangladesh were less in both the hospitals (42.85% in public hospital and 40.06% in private hospital).Conclusion: Average number of drugs per prescription was higher in both hospitals. Generic prescribing was lower in private hospital and prescribing from EDL was low in both hospitals.J Enam Med Col 2015; 5(3): 157-160